Institutions, Governance and the Control of Corruption (International Economic Association Series,, 2018)
This book considers how emerging economies around the world face the challenge of building good institutions and effective governance, since so much of economic development depends on having these in place. The promotion of shared prosperity and the battle against poverty require interventions to reach out to the poor and the disadvantaged. Yet time and again we have seen such effort foild or diminished by corruption and leakage. The creation of good governance and institutions and structures to combat corruption require determination and passion but also intricate design rooted in data, analysis, and research. In this book, leading researchers from around the world bring to the table some of the best available ideas to help create better governance structures, design laws for corruption control, and nurture good institutions.